A Case Study: An Analysis Of Bilingual Syllabus Design In Yamuda Bilingual Boarding School In Takengon) - Sarinauli, Barep; Gayo, Isnawi (Ta'dib: Jurnal Pemikiran Pendidikan, 2021)
This paper analyzed syllabus designed by second grade teacher of elementary level in Yamuda Bilingual Boarding School Takengon. The data employed were a document which was the syllabus and interview result of the English teacher and principal. This is a qualitative case study which analyzed the data by using coding system. The result shows that the English teacher as the designer of the syllabus perceived her collective-planned syllabus positively because it had met the need of her pupils to master the target language and face globalization. Individually, she has a shallow understanding in constructing an ideal syllabus. She might understand the format but not the crucial aspect of syllabus design. Out of six aspects to be reviewed, there are only five aspects fulfilled by her in the syllabus. Yet she did not insert the local content to the syllabus design. Moreover, the syllabus designer neither gave her students a balance diet of language skills nor language aspects. She missed to describe the method used in teaching and learning process and employed a small number of games. On the other hands, this syllabus is a theme-based syllabus design which do favor for young language learners to pick up foreign language; the teacher had a good time table of assessment in order to see her students’ progress during and after the course. Finally, she also mentioned the teaching objectives which directed her to expand her teaching material.